Simulation Study of Canal Switching in BPPV - Wu, Shuzhi; Li, Jianxin; Zhou, Mi; Yang, Xiaokai (Frontiers in Neurology, 2022)
The objective of this research was to investigate the mechanism of canal switching in benign paroxysmal positional vertigo through a virtual simulation model. Using Unity 3D software and a built-in NVIDIA Physx physics engine, the virtual simulation software is developed using a browser-server architecture, and different models are imported. Based on the benign paroxysmal positional vertigo virtual simulation model, we constructed five different virtual reality scenes of diagnosis and treatment, set otoliths in different positions of the semicircular canals, and analyzed the effects of diagnostic and therapeutic procedures on otolith location. Through the analysis of otolith movement in five virtual scenes, we found that canal switching may be caused by otoliths in the utricle entering the semicircular canal in the supine position. Then, we used different methods to reposition the otolith, improved the repositioning maneuver, and explored in depth the mechanism of the canal switching. The results showed that the main reason for the canal switch is that in the supine position, the otolith in the utricle enters the semicircular canal. The repositioning maneuvers, including the Epley maneuver and Barbecue maneuver, will not directly lead to the canal switch in the ipsilateral inner ear. The supine roll maneuver leads to the otolith in the utricle entering the posterior or lateral semicircular canal, which is the most likely mechanism for canal switching.